Retinoid-induced expression and activity of an immediate early tumor suppressor gene in vascular smooth muscle cells. - Jeffrey W Streb; Xiaochun Long; Ting-Hein Lee; Qiang Sun; Chad M Kitchen; Mary A Georger; Orazio J Slivano; William S Blaner; Daniel W Carr; Irwin H Gelman; Joseph M Miano (PLoS ONE, 2011)
Retinoids are used clinically to treat a number of hyper-proliferative disorders and have been shown in experimental animals to attenuate vascular occlusive diseases, presumably through nuclear receptors bound to retinoic acid response elements (RARE) located in target genes. Here, we show that natural or synthetic retinoids rapidly induce mRNA and protein expression of a specific isoform of A-Kinase Anchoring Protein 12 (AKAP12β) in cultured smooth muscle cells (SMC) as well as the intact vessel wall. Expression kinetics and actinomycin D studies indicate Akap12β is a retinoid-induced, immediate-early gene. Akap12β promoter analyses reveal a conserved RARE mildly induced with atRA in a region that exhibits hyper-acetylation. Immunofluorescence microscopy and protein kinase A (PKA) regulatory subunit overlay assays in SMC suggest a physical association between AKAP12β and PKA following retinoid treatment. Consistent with its designation as a tumor suppressor, inducible expression of AKAP12β attenuates SMC growth in vitro. Further, immunohistochemistry studies establish marked decreases in AKAP12 expression in experimentally-injured vessels of mice as well as atheromatous lesions in humans. Collectively, these results demonstrate a novel role for retinoids in the induction of an AKAP tumor suppressor that blocks vascular SMC growth thus providing new molecular insight into how retiniods may exert their anti-proliferative effects in the injured vessel wall.